2012
DOI: 10.3724/sp.j.1227.2012.00003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nitrogen addition on plant community in a semi-arid temperate steppe in China

Abstract: Increased nitrogen (N) deposition will often lead to a decline in species richness in grassland ecosystems but the shifts in functional groups and plant traits are still poorly understood in China. A field experiment was conducted at Duolun, Inner Mongolia, China, to investigate the effects of N addition on a temperate steppe ecosystem. Six N levels (0, 3, 6, 12, 24, and 48 g N/(m 2 ⋅a)) were added as three applications per year from 2005 to 2010. Enhanced N deposition, even as little as 3 g N/(m 2 ⋅a) above a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 26 publications
6
24
0
Order By: Relevance
“…Grasses, especially S. viridis , produced the majority of total biomass of the community, suggesting that grasses were the dominant functional group and S. viridis was the dominant species in this community. Grasses were more sensitive to nutrient addition and able to obtain more nutrients under the enrichment treatment, as observed in other studies9104445. As such, the resistance of the community to invasion may be attributed to the functional identity of resident competitors.…”
Section: Discussionsupporting
confidence: 70%
“…Grasses, especially S. viridis , produced the majority of total biomass of the community, suggesting that grasses were the dominant functional group and S. viridis was the dominant species in this community. Grasses were more sensitive to nutrient addition and able to obtain more nutrients under the enrichment treatment, as observed in other studies9104445. As such, the resistance of the community to invasion may be attributed to the functional identity of resident competitors.…”
Section: Discussionsupporting
confidence: 70%
“…Indeed, our data support this with alpha diversity (calculated based on 16S amplicon analysis at both DNA and RNA) decreasing in response to urea. This is inconsistent with plant responses to nutrient deposition in which multiple resources need to be added to elicit a response (Harpole & Stevens, ), although contrasting results have been observed (Bai, Wu, Clark, Naeem, & Pan, ; Song, Bao, Liu, & Zhang, ; Song et al., ; Suding et al., ). For microbes, high site to site variance is reported (De Schrijver et al., ; Leff et al., ), but similar negative responses are suggested and could be linked to increased competition in the absence of natural ecosystem variability.…”
Section: Discussionmentioning
confidence: 93%
“…For example, several studies have reported significant increases in the AGB of grasses and sedges 3, 23, 27 , significant decreases in the AGB of legumes 3, 27 , and insignificant changes in the AGB of forbs 27 following N addition. However, whether a general pattern of the responses of different plant functional types in grasslands to N addition exists at the global scale remains unclear.…”
Section: Introductionmentioning
confidence: 99%